Inhibitory effect of Zhujing Pill on myopia progression: Mechanistic insights based on metabonomics and network pharmacology. - Yongle Du; Mengran Pang; Haoyu Chen; Xiangkun Zhou; Ruyue Geng; Yanan Zhang; Linqi Yang; Jiawen Li; Yufeng Han; Jinpeng Liu; Ruixue Zhang; Hongsheng Bi; et al. (PLoS ONE)
Objectives This study endeavored to uncover the mechanisms by which Zhujing pill (ZJP) slows myopia progression. Methods We employed biometric analyses to track diopter and axial length changes in guinea pigs with negative lens-induced myopia (LIM). Through integrating metabonomics and network pharmacology, we aimed to predict the anti-myopic targets and active ingredients of ZJP. Subsequent analysis, including real-time fluorescent quantitative PCR (qPCR) and Western blotting (WB), assessed the expression levels of CHRNA7, LPCAT1, and NOS2 in retinal tissues. Key findings Our findings demonstrate that ZJP significantly mitigates diopter increase and axial elongation in LIM guinea pigs. Metabonomic analysis revealed significant changes in 13 serum metabolites, with ZJP reversing the expression of 5 key metabolites. By integrating metabonomics with network pharmacology, we identified core targets of ZJP against myopia and constructed a compound-gene-disease-metabolite network. The expressions of LPCAT1 and CHRNA7 were found to decrease in the LIM group but increase with ZJP treatment, whereas NOS2 expression showed the opposite pattern. Conclusions This investigation provides the first evidence of ZJP's multifaceted effectiveness in managing myopia, highlighting its impact on multiple components, targets, and pathways, including the novel involvement of LPCAT1 and CHRNA7 in myopia pathogenesis.